2019
DOI: 10.1186/s13063-019-3506-1
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a randomised controlled trial of CBT vs antipsychotics vs both in 14–18-year-olds: Managing Adolescent first episode Psychosis: a feasibility study (MAPS)

Abstract: Background Adolescent-onset psychosis is associated with more severe symptoms and poorer outcomes than adult-onset psychosis. The National Institute for Clinical Excellence (NICE) recommend that adolescents with first episode psychosis (FEP) should be offered a combination of antipsychotic medication (APs), cognitive behavioural therapy (CBT) and family intervention (FI). The evidence for APs in treating psychosis is limited in adolescents compared to adults. Nevertheless, it indicates that APs ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…It is a brief and straightforward self-report measure which assesses both depression and anxiety (Hansson et al, 2009) thus reducing the burden of completion for participants. It has been used in similar populations to ours, such as adolescents, young people and adults with psychosis (Bernard et al, 2006;White et al, 2011;Pyle et al, 2019), therefore allowing comparability of our results with similar studies.…”
Section: Secondary Outcomesmentioning
confidence: 93%
“…It is a brief and straightforward self-report measure which assesses both depression and anxiety (Hansson et al, 2009) thus reducing the burden of completion for participants. It has been used in similar populations to ours, such as adolescents, young people and adults with psychosis (Bernard et al, 2006;White et al, 2011;Pyle et al, 2019), therefore allowing comparability of our results with similar studies.…”
Section: Secondary Outcomesmentioning
confidence: 93%
“…Participants comprised thirteen YP who took part in MAPS and eighteen family members (sixteen interviews) at three study sites: North West, Oxfordshire, Sussex (see Table 1 for participant characteristics). MAPS participants were YP aged 14–18 years experiencing FEP (full inclusion and exclusion criteria are reported elsewhere [6] ). YP were eligible to take part in the qualitative study if they had already given consent to be audio-recorded, and family members were only approached if their young person agreed.…”
Section: Methodsmentioning
confidence: 99%
“…NICE Guidelines for treatment of psychosis in children and young people (CYP) [5] specifically call for research to test the comparative efficacy and safety of antipsychotic medication and psychological intervention in CYP. The Managing Adolescent first episode Psychosis (MAPS) study addressed this call by examining the feasibility of such a trial [6] . Sixty-one adolescents aged 14–18 with FEP were randomised to one of three treatment allocations: antipsychotics only (AP), psychological intervention only (cognitive behavioural therapy [CBT] and family intervention [FI]), or a combination of both.…”
Section: Introductionmentioning
confidence: 99%
“…Purposive sampling identified a representative range of eligible qualified mental health professionals with prescribing responsibility for adolescents with first episode psychosis (FEP) in UK Child and Adolescent Mental Health Services (CAMHS) or Early Intervention for Psychosis (EIP) services across NHS Trusts hosting the MAPS trial [ 4 , 5 ]. Potential participants were identified from MAPS trial liaison information (complete lists of local CAMHS and EIP prescribers), and invited to take part by email between October 2017 and July 2018.…”
Section: Methodsmentioning
confidence: 99%
“…However, the evidence to support this guidance is largely extrapolated from studies conducted with adults, which limits its value as treatment effects observed in adults, positive or negative, may occur differently in younger people. The MAPS feasibility trial (Managing Adolescent first Episode Psychosis: a feasibility Study) was developed to address the need to improve this evidence base [ 4 , 5 ]. MAPS randomised adolescents aged 14-18 years to one of three treatment allocations: AP only, CBT and FI only, or a combination of AP and CBT/FI.…”
Section: Introductionmentioning
confidence: 99%